Atomic mechanism of lithium dendrite penetration in solid electrolytes - Bowen Zhang; Botao Yuan; Xin Yan; Xiao Han; Jiawei Zhang; Huifeng Tan; Changuo Wang; Pengfei Yan; Huajian Gao; Yuanpeng Liu (Nature Communications)
Abstract Lithium dendrite penetration through ceramic electrolytes is known to result in mechanical failure and short circuits, which has impeded the commercialization of all-solid-state lithium anode batteries. However, the underlying mechanism still remains under debate, due in part to a lack of in situ atomic-level observations of the dendrite penetration process. Here, we employ molecular dynamics simulations to reproduce the dynamic process of dendrite nucleation and penetration. Our findings reveal that dynamically generated lithium depositions lead to a continuous accumulation of internal stress, culminating in fracture of the solid electrolyte at dendrite tips. We demonstrate that the classical Griffith theory remains effective in assessing this fracture mode, but it is necessary to consider the electrochemical impact of local lithium ion concentration on the fracture toughness. Additionally, in polycrystalline solid electrolytes, we observe that dendrite nuclei within grains typically deflect towards and propagate along grain boundaries. Simulations and experimental evidence both identify that dendrite induced fractures at grain boundaries exhibit a mixed Mode I and Mode II pattern, contingent on their fracture toughness and the angle between dendrites and grain boundaries. These insights deepen our understanding of dendrite penetration mechanisms and may offer valuable guidance for improving the performance of solid electrolytes.